Corporate Social Responsibility and Performance of Cirebon Hotels: A Moderation by CSR Strategy and Gender - Reka Risdiana; Chintia Isqifaradillah; Acep Komara (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study explores how implementing Corporate Social Responsibility (CSR) influences hotel performance in Cirebon, with CSR strategy and gender diversity as moderating variables. A quantitative approach was employed by surveying 20 three- and four-star hotels. The findings indicate a statistically significant positive correlation between CSR activities and the performance of hotels. CSR strategy strengthens this relationship, while gender diversity at the managerial level enhances the effectiveness of CSR implementation. These findings underscore the significance of a structured CSR strategy and gender-inclusive management in maximising the impact of CSR on hotel performance.